Conflict over the Norms of Inter-Religious Marriage: Challenges in Integrating Human Rights - Faisol, Syahid; Heppy, Heppy Hyma Puspytasari; Hermono, Budi; Hikmah, Nurul; Astrid Amidiaputri Hasyyati (PT. Inovasi Teknologi Komputer, 2024)
Marriage is a legal event which is a right for every person in Indonesia. According to Article 2 paragraph (1) of Law Number 1 of 1974 concerning marriage, a marriage is valid if it is carried out according to the laws of each respective religion and belief. This norm provides an understanding that a marriage will be recognized by the state if it is carried out by a man and a woman under the same religion, the promise is recorded afterwards as intended in Article 2 paragraph (2) of the UUP. Registration at the civil registry office accepts registration of inter-religious marriages as regulated in Article 35 letter a of Law no. 23 of 2006 in conjunction with Law no. 24 of 2013 concerning Population Administration through Court permission. Furthermore, the Supreme Court issued SEMA No. 2 of 2023 concerning Instructions for Judges in Adjudicating Marriage Cases between People of Different Religions and Beliefs. This article discusses the conflict of norms that arise in the arrangement of interfaith marriages in Indonesia, especially in the context of the integration of human rights. By using juridical and social analysis. The main focus is on the influence of SEMA No. 2 of 2023 regarding legal certainty and harmonization in marriage arrangements in Indonesia. The results of this research show a conflict of norms between Law no. 1 of 1974 concerning Marriage which regulates norms prohibiting interfaith marriages implicitly and Law no. 23 of 2006 concerning population administration which provides opportunities for legalizing interfaith marriages. The challenges faced in integrating regulations and human rights show that judges have different views in determining requests for interfaith marriages, which in the end can have legal and social impacts on society